Carbon nanotube bumps for the flip chip packaging system - Yap, Chin Chong (2013)
Carbon nanotube [CNT] interconnection bump joining methodology has been successfully demonstrated using flip chip test structures with bump pitches smaller than 150 μm. In this study, plasma-enhanced chemical vapor deposition approach is used to grow the CNT bumps onto the Au metallization lines. The CNT bumps on the die substrate are then 'inserted' into the CNT bumps on the carrier substrate to form the electrical connections (interconnection bumps) between each other. The mechanical strength and the concept of reworkable capabilities of the CNT interconnection bumps are investigated. Preliminary electrical characteristics show a linear relationship between current and voltage, suggesting that ohmic contacts are attained.